Readiness for Family Life as a Problem - qizi, Baxtiyorova Munira Mansur (European Journal of Life Safety and Stability (2660-9630), 2023)
An important task of preparing for family life is to form an adequate relationship between young men and women in the field of family and marital relations. In order to effectively fulfill future family and marital roles, information is provided that a young person should have a strong, happy family and a positive relationship system aimed at responsible performance of family tasks (reproductive, educational, economic, etc.).